Instructional Scheduling and Teacher Competence as Predictors of Emotional Intelligence and Learning Interest in Physical Education - Farid M. Alhumary; Benny Aprial M; Muhammad Isnandar (Institut Teknologi Pendidikan Indonesia, 2026)
This study investigates the simultaneous influence of class scheduling and educator competencies on secondary school students' affective learning outcomes. Utilizing an ex post facto design with quantitative descriptive approach, data were collected from 330 high school students (165 morning session, 165 afternoon session) and 15 physical education teachers across five public schools in Medan, Indonesia. Cluster sampling technique was employed to select participants. Data gathering instruments included validated questionnaires for emotional intelligence (25 items, α = 0.819), learning interest (31 items, α = 0.901), and teacher competence rubrics. Independent sample t-tests and simple linear regression analyses revealed statistically significant differences between morning and afternoon cohorts in emotional intelligence (ΔM = 2.697, t = 3.300, p < 0.05) and learning interest (ΔM = 5.006, t = 4.813, p < 0.05). Furthermore, teacher competence demonstrated substantial positive correlations with both emotional intelligence (R² = 0.782, t = 3.277, p = 0.047) and student interest (R² = 0.796, t = 3.426, p = 0.042). These findings suggest that optimal scheduling of physical education classes in morning sessions combined with enhanced teacher professional competencies contribute significantly to students' socio-emotional development and academic motivation.